Two Tales of A Single City - New Urban Cultural Studies Perspectives on New York City (KULT_online, 2016)
The monographs of James Peacock and Christoph Lindner both add to the urban studies scholarship on the city of New York, yet with two distinctly different foci and respective interdisciplinary approaches. James Peacock’s Brooklyn Fictions: The Contemporary Urban Community in a Global Age marks the first treatment of the New York City borough of Brooklyn and literary representations of it as singular and separate from its dominant neighboring borough, Manhattan, thus closing a gap in existing scholarship on New York City. By contrast, Christoph Lindner’s Imagining New York City: Literature, Urbanism, and the Visual Arts, 1890-1940, as should be apparent from its title, takes the whole city of New York as its field of inquiry while impressing with an innovative structure and a convincing interdisciplinary approach.